The metastasis-associated molecule C4.4A promotes tissue invasion and anchorage independence by associating with the alpha6beta4 integrin - Thuma, Florian; Ngora, Honoré; Zöller, Margot (Molecular oncology, 2013)
C4.4A is a metastasis-associated molecule that functions appear to rely on associated alph6beta4 integrin. To corroborate the impact of the C4.4A-alpha6beta4 integrin association on metastasis formation, C4.4A was knocked-down in a highly metastatic rat pancreatic adenocarcinoma (ASML, ASML-C4.4Akd). Metastasis formation by ASML-C4.4Akd cells after intrafootpad application was strongly retarded in draining nodes and lung colonization was rare. Furthermore, cisplatin treatment significantly prolonged the survival time only of ASML-C4.4Akd-bearing rats. ASML-C4.4Akd cells display reduced migratory activity and impaired matrix protein degradation due to inefficient MMP14 activation; loss of drug-resistance is due to mitigated PI3K/Akt pathway activation. These losses of function rely on the laminin receptor C4.4A recruiting activated alpha6beta4 integrin into rafts, where C4.4A cooperates with alpha6beta4 and via alpha6beta4 with MMP14. Within this raft-located complex, MMP14 provokes focalized matrix degradation and mostly alpha6beta4 integrin promotes BAD phosphorylation and upregulated Bcl2 and BclXl expression. Thus, metastasis-promoting activities of C4.4A are not genuine characteristics of C4.4A. Instead, the raft-located laminin receptor C4.4A recruits alpha6beta4 integrin and supports via the alpha6beta4 integrin MMP14 activation. Thereby C4.4A acts as a linker to facilitate several steps in the metastatic cascade. Taking the restricted C4.4A expression in non-transformed tissue, this knowledge should pave the way toward the use of C4.4A as a therapeutic target.